The Effect of Training Model and Agility on Dribbling Ability in Terawas FC Football School Players Age 14-16 Years in Lubuklinggau City (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Terawas FC football players aged 14 to 16 have very low dribbling skills. This study’s primary objective is to compare the effectiveness of the diamond with ball and diamond with run training models. Differential effects of high and low agility and the interaction between training models and agility on dribbling ability. The method in this study uses a quasi-experimental method with a design factor of 2x2. There are 42 players, with an average age of 14 to 16 years. The sampling menthod used was purposive sampling with a sample size of 28 individuals, and the Two-Way Anova test was used to analyze the data. 1) Determine whether the practice of diamond with the ball or diamond with the run has a greater impact on agility with a value of Fcount (97.923) > Ftable (0.720). 2) To distinguish between high and low dribbling agility with a value of Fcount (23.384) > Ftable (0.720). 3). Determine the difference between the practice of diamond with the ball and diamond with the run on the ability to dribble using Fcount (27.645) > Ftable (0.720). 4). To determine the difference between the diamond with the ball and the diamond with the run, training models with a value of Fcount (48.895) > Ftable (0.720). 5). To determine that there is no interaction between the diamond with the ball and diamond with the run training models and high and low agility on the ability to dribble using Fcount (24.900) > Ftable (0.720). The conclusion is that diamond with the ball and diamond with the run training models influence the agility and dribbling ability of Lubuklinggau City Terawas FC football school players aged 14 to 16 years.